2013
DOI: 10.1080/09540121.2013.793276
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence and subjective well-being in HIV/AIDS infection

Abstract: The aim of this study was to analyze the relationship between treatment adherence and subjective well-being (positive and negative affects and satisfaction with life) in HIV/AIDS infection. The empirical study was conducted at two Portuguese hospitals (Porto and Lisbon) with a sample of 197 outpatients diagnosed with HIV/AIDS attending the Infectology service and on antiretroviral medication, during a 6-month period (February-July 2009). All patients were asked for voluntary fulfillment of the questionnaire wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
2
14
0
1
Order By: Relevance
“…Good medication adherence was negatively associated with poor SWB in this study. Similar finding was reported in other chronic illness [ 43 ]. Good adherence was also reported to be associated with improved health outcomes and hence positive SWB [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…Good medication adherence was negatively associated with poor SWB in this study. Similar finding was reported in other chronic illness [ 43 ]. Good adherence was also reported to be associated with improved health outcomes and hence positive SWB [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…Currently there is no research on the relationship between subjective well-being and HIV testing. However, findings from a study in Portugal suggested subjective well-being is correlated with adherence to antiretroviral medication, indicating its importance in the scope of treatment and living with HIV [22]. In their study, Reis, Guerra, and Lencastre [22] found that patients with greater subjective well-being were more likely to be asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…However, findings from a study in Portugal suggested subjective well-being is correlated with adherence to antiretroviral medication, indicating its importance in the scope of treatment and living with HIV [22]. In their study, Reis, Guerra, and Lencastre [22] found that patients with greater subjective well-being were more likely to be asymptomatic. Given its impact on how people living with HIV cope and adhere to medication regimens, subjective well-being is a factor of interest among the HIV research community.…”
Section: Introductionmentioning
confidence: 99%
“…Rzeszutek et al ( 2015 ) showed that longer HIV infection duration may intensify PTSSs, but perceived availability of social support may be a buffer against HIV-related trauma symptoms in PLWHA. Other studies have shown that treatment adherence (Drozd et al 2014 ), a web-based intervention trial in patients with chronic HIV infection (Reis et al 2013 ) and optimism (Ammirati et al 2015 ) may have a positive impact on SWB in PLWH.…”
Section: Introductionmentioning
confidence: 99%